Evaluation of Nucleated Red Blood Cell Morphology Flag Screening with ADVIA® 2120 - R. Mustarichie (Journal of Global Pharma Technology, 2020)
The evaluation of nucleated red blood cell morphology flag screening with ADVIA® 2120 on behalf of blood smear has been investigated. The accurate and timely reporting of nucleated red blood cells (NRBC) is an important function of the clinical hematology laboratory because the presence of NRBC in human peripheral blood can show a special clinical status. It has been used 40 samples to evaluate an NRBC screening for the ADVIA® 2120 Hematology System with peripheral blood smears. The positive samples have a criteria % NRBC in range 0 – 15%. (in 100 leucocytes). The sensitivity and specificity for the presence of NRBC for all samples analyzed was 90 % and 63,33 %, respectively. There is a correlation on NRBC result screening between ADVIA® 2120 and peripheral blood smears with α 0,003 of spearman correlation. Keywords: Nucleated red blood cell (NRBC, flag, Clinical test, ADVIA® 2120.